Listening to Children’s Voices: Reflections on Researching With Children in Multilingual Montreal - Alison Crump; Heather Phipps (LEARNing Landscapes, 2013)
In this paper, we discuss methodological and ethical issues related to researching with children in a way that respects and validates their voices. Drawing on vignettes from one of the author’s inquiries with young multilingual children, we share strategies we see as central to positioning children as knowledgeable and active agents in their own and our learning. We propose three main criteria for doing qualitative research with children: fostering respectful relationships; using creative methods; and listening attentively to children’s stories. We discuss what these criteria can contribute to early childhood education, both in formal and non-formal settings.